SEBARAN DAN KELIMPAHAN KUKANG JAWA (Nyticebus javanicus) DI TAMAN WISATA ALAM GUNUNG TAMPOMAS - Purwanto, Asep; Rosyidin, Hilman (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
The observation of distribution and abundance of Javan slow loris (Nycticebus javanivus) was carried out in Sumedang district area (West Java), which includes at TWA Gunung Tampomas. The objective of the research is to investigate the distribution and abundance of Javan slow loris at side and outside of protected forest in support the conservation management of slow loris. Observation location was between protected forest and agricultural area an altitude of 600 to 900 m above sea level. The result only on the three lines transect Javan Slow loris were found with total 11 individual. The population is less than the population outside the site research. Twenty-six individuals of Javan slow loris were found in community’s plantation which vegetation dominated by bamboo trees and agriculture plantation.